Problems and difficulties facing Zakat administration / Khairul Azman Aziz and Mohamad Azmi Nias Ahmad - Aziz, Khairul Azman; Ahmad, Mohamad Azmi Nias (Universiti Teknologi MARA Cawangan Pahang, 2002)
This paper outlines nine areas of problems and difficulties facing zakat administration in Malaysia. The nine areas are Fiqhi related problems, coverage of Zakat, Zakat assessment, Zakat payment through non-official channels, information gap, storage and transportation, administrative cost, disbursement of Zakat and Zakat law. The problems outlined should not be considered as hindrance to the practice of Zakat. Rather, they should be considered as hurdles where if resolved, the benefits of Zakat will truly be realized.